2007
DOI: 10.3354/meps07138
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries-induced evolutionary changes in maturation reaction norms in North Sea sole Solea solea

Abstract: Age and size at maturation decreased in several commercially exploited fish stocks, which, according to life history theory, may be due to fisheries-induced evolutionary change. However, the observed changes may also represent a plastic response to environmental variability. To disentangle phenotypic plasticity from evolutionary change, the probabilistic reaction norm approach was applied to 43 cohorts (1960 to 2002) of female sole Solea solea from market samples. The reaction norm for age and size at first ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 44 publications
(68 reference statements)
7
79
2
Order By: Relevance
“…Among the potential sources of growth-independent plasticity examined, only temperature had a significant effect on female cod maturation; temperature experienced at age 0 had a significant negative effect on female cod L p50 at age 3, in agreement with earlier work (Wright et al 2011b, Neuheimer & Grønkjaer 2012. Previous findings for North Sea plaice and sole have also shown that elevated temperatures may accelerate maturation (Grift et al 2003, Mollet et al 2007). Evidence of short-term temperature effects can also be found in the time series: around the years 1987 to 1989, temperatures exhibited a peak (Fig.…”
Section: Temporal Trends In Pmrnssupporting
confidence: 80%
See 2 more Smart Citations
“…Among the potential sources of growth-independent plasticity examined, only temperature had a significant effect on female cod maturation; temperature experienced at age 0 had a significant negative effect on female cod L p50 at age 3, in agreement with earlier work (Wright et al 2011b, Neuheimer & Grønkjaer 2012. Previous findings for North Sea plaice and sole have also shown that elevated temperatures may accelerate maturation (Grift et al 2003, Mollet et al 2007). Evidence of short-term temperature effects can also be found in the time series: around the years 1987 to 1989, temperatures exhibited a peak (Fig.…”
Section: Temporal Trends In Pmrnssupporting
confidence: 80%
“…(B) For a positively sloped PMRN approached from below by length-at-age curves, faster growth rates result in younger ages at maturation and smaller sizes at maturation. (C) When length-at-age curves approach the PMRN from above, which is possible for a positively sloped PMRN only, faster growth rates result in older ages at maturation and larger sizes at maturation temporal trend in maturation (Grift et al 2007, Mollet et al 2007). Unfortunately, we could not include such an index in our analyses because individual weights were not available.…”
Section: The Pmrn Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to their economic importance, increased fishing pressure has resulted in a drastic drop of flatfish landings with some difficulties to meet the current demands (ICES 2008). Also, overexploitation of wild stocks has reduced genetic diversity in plaice (Hoarau et al 2005), and is thought to underlie modified life-history traits with a shift towards earlier sexual maturation at smaller size in sole and plaice (Mollet et al 2007;van Walraven et al 2010). As a consequence, the development of aquaculture for some of these species has been proposed to supplement the demands for human consumption while reducing the pressure on natural populations.…”
Section: The Aquaculture Of Flatfishmentioning
confidence: 99%
“…More recently, a number of empirical studies have estimated probabilistic maturation reaction norms (Heino et al 2002) for numerous fish stocks: these indeed turned out to be domeshaped, or roughly linear, with negative global slopes (Grift et al 2003(Grift et al , 2007Engelhard and Heino 2004;Olsen et al 2004Olsen et al , 2005Barot et al 2005;Mollet et al 2007). Only very few probabilistic maturation reaction norms have been reported to exhibit positive slope (Heino et al 2002) or to be roughly flat (Barot et al 2004).…”
Section: Comparison With Empirical Knowledgementioning
confidence: 99%